2018
DOI: 10.1016/j.reth.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Autologous and heterotopic transplantation of adipose stromal vascular fraction ameliorates stress urinary incontinence in rats with simulated childbirth trauma

Abstract: IntroductionAutologous transplantation of adipose stromal vascular fraction (SVF) is a cost-effective and technically accessible option for cell therapy. Clinical study of SVF transplantation for male stress urinary incontinence (SUI) is underway, but the effectiveness remains unknown for female SUI, majority of which is caused by childbirth trauma.MethodsVaginal Distension (VD) rats were generated as in vivo model for female SUI. To quantitate the severity of SUI, leak point pressure (LPP) was measured by pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…ADRCs isolated with the Celution system were composed of a heterogeneous cell population including adipose stem cells, and were also reported to show pluripotency and secretion of cytokines . Based on preclinical experimental injection of adipose stem cells or ADRCs into the rat urethra, it was suggested that the mechanisms involved in the improvement of sphincter function included a bulking effect, regeneration of smooth muscle and increased blood flow caused by adipose stem cells or ADRC injection, as also confirmed by our previous clinical study . We are carrying out further analysis of cell characteristics using human ADRCs isolated with the Celution system.…”
Section: Discussionsupporting
confidence: 63%
“…ADRCs isolated with the Celution system were composed of a heterogeneous cell population including adipose stem cells, and were also reported to show pluripotency and secretion of cytokines . Based on preclinical experimental injection of adipose stem cells or ADRCs into the rat urethra, it was suggested that the mechanisms involved in the improvement of sphincter function included a bulking effect, regeneration of smooth muscle and increased blood flow caused by adipose stem cells or ADRC injection, as also confirmed by our previous clinical study . We are carrying out further analysis of cell characteristics using human ADRCs isolated with the Celution system.…”
Section: Discussionsupporting
confidence: 63%
“…The previous basic and exploratory clinical study suggested that the mechanisms of action of this treatment are differentiation of the injected cells to smooth muscle cells, an increase in blood flow caused by an increase in vascularization as a result of cytokine production by the injected cells and maintenance of the bulking effect by the injected adipose tissue combined with ADRCs 17,18 . Inoue et al also reported that injection of uncultured autologous stromal vascular fractions to the external urethral sphincter improves the urethral sphincteric function, and increases anti‐smooth muscle antibody positive cells and collagen synthesis in a rat SUI model 22 . This hypothesis was partly confirmed in the secondary outcomes of this study; evaluation of blood flow by the transrectal enhanced ultrasonography in this study showed the progressive increase of blood flow at the injection site, MUCP increased and also magnetic resonance imaging analysis showed the injected adipose tissue around the urethra was maintained with minimal absorption at 52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ADSC, the preparation of SVF is even simpler, with single protease digestion yielding 2–6 × 10 6 SVF cells (CSVF) per 1 mL of fat with ≥90% cell viability. Many studies have shown that ADSC and CSVF can promote tissue repairs, such as skeletal tissue [ 28 , 29 , 30 , 31 ], muscle tissue [ 32 , 33 , 34 ], nerve damage [ 35 , 36 , 37 , 38 ], and cardiovascular injury [ 39 , 40 , 41 ]. Meanwhile, the tissue source of ADSC and CSVF is widely available, and a large amount of adipose tissue can be obtained for ADSC and CSVF extraction during liposuction, manual liposuction, etc., while the invasive procedure in obtaining bone marrow MSC and muscle-derived stem cells have limited their application in clinic.…”
Section: Introductionmentioning
confidence: 99%